Tutors’ chronological age and characteristics as predictors of creative nurturing behavior in the 21st-century classroom - Mahama, Inuusah; Dampson, Dandy George; Eshun, Peter (Frontiers in Education, 2023)
The study explored how tutors’ characteristics and age influence their creativity nurturing behaviours. The descriptive cross-sectional design was used to survey 340 tutors (male=220, female=120) from 16 Colleges of Education. The data for the study were gathered using adapted versions of teachers’ characteristics and creativity nurturing behaviours scales. The data were analysed inferentially. The study revealed that tutors’ characteristics influenced their creativity nurturing behaviours [β = .307, t = 9.59, 95% CI (.244, .370)] and teachers with 30 years and above of teaching could influence their creativity nurturing behaviours [β = .207, t = 3.76, 95% CI (38.86, 48.04)]. Differences were established in tutors’ creativity nurturing behaviours (CNB [F (3, 336) =45.04, p<.000]) based on their experience but such were not found in tutors’ characteristics. It was concluded that tutors’ characteristics and age are two key drivers of their creative abilities in the 21st century classroom. Therefore, management of teacher training institutions must cultivate an appreciable and appropriate characteristics and disposition among their tutors so that they can use them to nurture trainee-teachers.